2022
DOI: 10.20885/jielariba.vol8.iss2.art2
|View full text |Cite
|
Sign up to set email alerts
|

Amil Zakat Institutions Performance Analysis During the Covid-19 Pandemic: Studies in Indonesia, Singapore, and England

Abstract: The Amil Zakat Institution is required to have efficient and effective performance, especially during the Covid-19 health crisis. This study aims to measure the performance of amil zakat institutions in Indonesia, Singapore, and England based on the efficiency level with the Data Envelopment Analysis approach and the level of effectiveness with the Allocation to Collection Ratio approach. The efficiency level of amil institutions was measured using the Data Envelopment Analysis method, the non-parametric stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Some studies have examined how Zakat institutions have responded to the pandemic. For example, a study conducted in Indonesia found that Zakat institutions increased their distribution of Zakat funds during the pandemic to help those affected by the crisis (Akram H et al, 2022;Hakim & Setyaningsih, 2022;Hasan & Kamiluddin, 2021;Hudaefi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have examined how Zakat institutions have responded to the pandemic. For example, a study conducted in Indonesia found that Zakat institutions increased their distribution of Zakat funds during the pandemic to help those affected by the crisis (Akram H et al, 2022;Hakim & Setyaningsih, 2022;Hasan & Kamiluddin, 2021;Hudaefi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zakat distribution can be carried out in various ways depending on the management policies of the zakat institution. Sometimes it is distributed directly to the mustahik (those eligible to receive zakat) through consumptive models, and sometimes it is realized in productive forms as seen during the time of the Prophet, or by providing capital or zakat developed through investment models (Akram H et al, 2022;Maguni, 2013;Wahyuni, 2016).…”
Section: Introductionmentioning
confidence: 99%